Characterization of an amphioxus paired box gene, AmphiPax2/5/8: developmental expression patterns in optic support cells, nephridium, thyroid-like structures and pharyngeal gill slits, but not in the midbrain-hindbrain boundary region - Kozmik, Z; Holland, N D; Kalousova, A; Paces, J; Schubert, M; Holland, L Z (Development (Cambridge, England), 1999)
On the basis of developmental gene expression, the vertebrate central nervous system comprises: a forebrain plus anterior midbrain, a midbrain-hindbrain boundary region (MHB) having organizer properties, and a rhombospinal domain. The vertebrate MHB is characterized by position, by organizer properties and by being the early site of action of Wnt1 and engrailed genes, and of genes of the Pax2/5/8 subfamily. Wada and others (Wada, H., Saiga, H., Satoh, N. and Holland, P. W. H. (1998) Development 125, 1113-1122) suggested that ascidian tunicates have a vertebrate-like MHB on the basis of ascidian Pax258 expression there. In another invertebrate chordate, amphioxus, comparable gene expression evidence for a vertebrate-like MHB is lacking. We, therefore, isolated and characterized AmphiPax2/5/8, the sole member of this subfamily in amphioxus. AmphiPax2/5/8 is initially expressed well back in the rhombospinal domain and not where a MHB would be expected. In contrast, most of the other expression domains of AmphiPax2/5/8 correspond to expression domains of vertebrate Pax2, Pax5 and Pax8 in structures that are probably homologous - support cells of the eye, nephridium, thyroid-like structures and pharyngeal gill slits; although AmphiPax2/5/8 is not transcribed in any structures that could be interpreted as homologues of vertebrate otic placodes or otic vesicles. In sum, the developmental expression of AmphiPax2/5/8 indicates that the amphioxus central nervous system lacks a MHB resembling the vertebrate isthmic region. Additional gene expression data for the developing ascidian and amphioxus nervous systems would help determine whether a MHB is a basal chordate character secondarily lost in amphioxus. The alternative is that the MHB is a vertebrate innovation.
Keywords: molekulární evoluce; alternativní sestřih; ucho; exprese genu; DNA-Binding Proteins; sekvence nukleotidů; Gills; Gene Expression; DNA vazebné proteiny; Eye; Sequence Homology; Chordata, Nonvertebrate; Sequence Analysis, DNA; Molecular Sequence Data; Transcription Factors; Evolution, Molecular; molekulární sekvence - údaje; ledviny; sekvence aminokyselin; oči; Thyroid Gland; Kidney; žábry; zvířata; Ear; štítná žláza; Alternative Splicing; nižší strunatci; sekvenční analýza DNA; Amino Acid Sequence; mozkový kmen; rozvržení tělního plánu; Base Sequence; Photoreceptor Cells, Invertebrate; Body Patterning; fotoreceptory bezobratlých; Brain Stem; transkripční faktory; Animals; multigenová rodina; Multigene Family; sekvenční homologie